Increase in premature mortality due to non-communicable diseases in Sri Lanka during the first decade of the twenty-first century - Dileepa Senajith Ediriweera; Palitha Karunapema; Arunasalam Pathmeswaran; Mahendra Arnold (BMC, 2018)
Abstract Background Globally, non-communicable diseases (NCD) are the leading cause of death and more than 40% of NCD deaths are premature occurring before the age of 70 years. In 2012, World Health Assembly declared its commitment to reduce premature NCD mortality by 25% from 2010 to 2025. The trend of premature NCD deaths in Sri Lanka has not been assessed and thus this study was done to assess it between 2001 to 2010. Methods Deaths due to cardiovascular diseases, cancers, chronic respiratory diseases and diabetes were studied. Premature NCD mortality was assessed using unconditional probability of dying (UPoD) due to NCDs among those aged 30 to 70 years. Number of relevant premature NCD deaths that occurred in each 5-year age interval and the respective mid-year population was used to calculate UPoD. Results During the period of 2001 to 2010, premature NCD mortality in Sri Lanka increased from 15·8% to 19·1% and males showed higher mortality compared to females throughout the period. Highest mortality was due to cardiovascular diseases followed by cancer and diabetes and all three showed an increasing trend. Chronic respiratory diseases showed an increase until 2004 and dropped thereafter. Among the four NCDs, diabetes revealed the most marked increasing trend in premature mortality during this period. Conclusions The data revealed an increasing trend of premature NCD mortality in Sri Lanka between 2001 and 2010 although it has a relatively lower premature NCD mortality rate in the South-East Asian Region. Therefore, reducing premature NCD mortality by 25% from 2010 to 2025 is likely to be a rather challenging task in Sri Lanka and policy level changes need to be taken to achieve this target.